(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
This work aims to present an analysis from the standpoints of Skinner’s radical behaviorism about the variables involved in the psychiatric problems denominated as anxiety disorder. At first, anxiety is defined as a clinical phenomenon and as a theoretical construct. The behavioral literature emphasizes avoidance and elimination responses, and the selection of standardized therapeutic procedures due to that emphasis. They are then discussed considering the current non-observance of other environmental relevant variables. The article suggests that other functional relationships than avoidance can be detected, as focus of the intervention. Respondent and operant relationships that compose the client’s behavior repertoire that is diagnosed as anxiety disorder are analyzed, including the interaction among operant and respondent contingencies, aversive control, stimuli control, superior order response classes and establishing operations such as privation and aversive stimulation. At last, a model that integrates the relationships involved in the clinical patterns in focus is presented and possible therapeutic strategies are suggested.